Microwave And Reflection Properties Of Palm Shell Carbon-Polyester Conductive Composite Absorber - Yusof, Ahmad Anas; Wan Ali, Wan Khairuddin; Abd. Rahman, Tharek; Ani, Farid Nasir (Penerbit UTM Press, 2005)
The Microwave Properties Of Permittivity, å And Loss Tangent, Tan ä Of Conductive Composite Utilizing Palm Shell Carbon Mixed With Unsaturated Polyester Resin Were Studied In The 8 To 12 Ghz Frequency Range. The Measurement Of å And Tan ä Emphasize On The Influence Of Carbon Concentration (Mass %) Of Palm Shell Pyrolysed At 600, 700 And 800°C. It Was Observed That The Increase Of Carbon Concentration Inside Each Measured Composite Influenced The Increase Of å And Tan ä Condition. A Microwave Reflectivity Test Was Also Conducted By Using 30% Palm Shell Carbon In A 450 . 450 Mm Polyester Composite Panel. The Result Indicated That The Composite Thickness Had Influenced The Reflection Loss Curve Throughout The Same Microwave Frequencies. The Reflection Loss Up To –20 Db Was Possible In Specific Effective Frequency Ranges. This Indicated The Possibility Of Using Carbon Derived From Palm Shell Residue In Providing Significant Loss That Contributed To Microwave Absorption, As Well As An Alternative In Managing The Increased Of Oil Palm Shell Residues Throughout The Country.